Post 2010 Afghanistan-Pakistan’s Transit Trade: Implications of Legal and Illegal Endeavours - Shah, Syed Subtian Hussain (Journal of Education Culture and Society, 2018)
Aim. The aim of this article is to analyse legal and illegal trade between Afghanistan and Pakistan in the post 2010 era. According to the complex interdependence, the region is witnessing a regional security complex and the relationship between the actors is characterised by both cooperation and competition (Rana, 2015). In these circumstances, the national security defines in a narrower sense of protection of a nation from physical attack and safeguarding its economic activities from devastating outside threats (Gandhi, 2010). Both Pakistan and Afghanistan are pursuing their own national interests in the context of national security and sometimes, their national security interests compete with each other.Method. The qualitative method of research was employed to analyse the implications of legal and illegal trade between Afghanistan-Pakistan in post 2010 era. The data was collected from different sources including books, scientific journals, research articles, newspapers and websites.Results. By using various valuable references, it has been verified that beside the political and geological factors, low prices of the smuggled items and corruption are also main reasons of exploitation of the Afghan’s transit trade. It has created bad impact on Pakistan’s economy and well as it is still threatening other national interests of the country.Conclusion. The study confirms that the menace of smuggling can be decreased through durable policies and well-connected measures. A checks and balances system should be activated in the context in Pakistan and differences with Afghanistan’s government should be decreased through a bilateral dialogue process.